Fabrication and Wettability Study of WO3 Coated Photocatalytic Membrane for Oil-Water Separation: A Comparative Study with ZnO Coated Membrane - Gondal, Mohammed A.; Sadullah, Muhammad S.; Qahtan, Talal F.; Dastageer, Mohamed A.; Baig, Umair; McKinley, Gareth H. (Scientific Reports, 2017)
Superhydrophilic and underwater superoleophobic surfaces were fabricated by facile spray coating of nanostructured WO3 on stainless steel meshes and compared its performance in oil–water separation with ZnO coated meshes. The gravity driven oil-water separation system was designed using these surfaces as the separation media and it was noticed that WO3 coated stainless steel mesh showed high separation efficiency (99%), with pore size as high as 150 µm, whereas ZnO coated surfaces failed in the process of oil-water separation when the pore exceeded 50 µm size. Since, nanostructured WO3 is a well known catalyst, the simultaneous photocatalytic degradation of organic pollutants present in the separated water from the oil water separation process were tested using WO3 coated surfaces under UV radiation and the efficiency of this degradation was found to be quite significant. These results assure that with little improvisation on the oil water separation system, these surfaces can be made multifunctional to work simultaneously for oil-water separation and demineralization of organic pollutants from the separated water. Fabrication of the separating surface, their morphological characteristics, wettability, oil water separation efficiency and photo-catalytic degradation efficiency are enunciated.
EPrint Processing Status: Full text deposited in DRO